Long non‐coding RNAs as potential biomarkers in the prognosis and diagnosis of lung cancer: A review and target analysis - Aftabi, Younes; Ansarin, Khalil; Shanehbandi, Dariush; Khalili, Majid; Seyedrezazadeh, Ensiyeh; Rahbarnia, Leila; Asadi, Milad; Amiri‐Sadeghan, Amir; Zafari, Venus; Eyvazi, Shirin; Bakhtiyari, Nasim; Zarredar, Habib (IUBMB life, 2021)
Long non‐coding RNAs (lncRNA) have been emerged as a novel class of molecular regulators in cancer. They are dysregulated in many types of cancer; however, there is not enough knowledge available on their expression and functional profiles. Lung cancer is the leading cause of the cancer deaths worldwide. Generally, lncRNAs may be associated with lung tumor pathogenesis and they may act as biomarkers for the cancer prognosis and diagnosis. Compared to other invasive prognostic and diagnostic methods, detection of lncRNAs might be a user‐friendly and noninvasive method. In this review article, we selected 27 tumor‐associated lncRNAs by literature reviewing to further discussing in detail for using as diagnostic and prognostic biomarkers in lung cancer. Also, in an in silico target analysis, the “Experimentally supported functional regulation” approach of the LncTarD web tool was used to identifying the target genes and regulatory mechanisms of the selected lncRNAs. The reports on diagnostic and prognostic potential of all selected lncRNAs were discussed. However, the target genes and regulatory mechanisms of the 22 lncRNAs were identified by in silico analysis and we found the pathways that are controlled by each target group of lncRNAs. They use epigenetic mechanisms, ceRNA mechanisms, protein interaction and sponge mechanism. Also, 10, 23, 5, and 28 target genes for each of these mechanisms were identified, respectively. Finally, each group of target genes controls 50, 12, 7, and 2 molecular pathways, respectively. In conclusion, LncRNAs could be used as biomarkers in lung cancer due to their roles in control of several signaling pathways related to lung tumors. Also, it seems that lncRNAs, which use epigenetic mechanisms for modulating a large number of pathways, could be considered as important subjects for lung cancer‐related diagnostic and prognostic biomarkers.